2012
DOI: 10.1186/0778-7367-70-5
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practices of people in Bia District, Ghana, with regard to iodine deficiency disorders and intake of iodized salt

Abstract: BackgroundDespite numerous educational programmes to create awareness about iodized salt and iodine deficiency disorders (IDD), a survey conducted in the Western Region of Ghana in 2007 revealed that the goitre rate stood at 18.8%; and 78.1% of households consumed iodized salt, which is below the goal of the IDD programme in Ghana which aimed at 90% household consumption of iodized salt by the end of 2005 and sustaining the gains by 2011. It was therefore, considered timely to investigate the knowledge levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
49
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 9 publications
8
49
6
Order By: Relevance
“…However, this finding is lower than the findings from India 60.1% [23], Albania 60.41% [13], Ghana 75.6% [24], Kazakhstan 77.3% [25], and Nigeria 91% [26] of the households that were using adequately iodized salt. The explanation for the higher proportion of iodized salt consumption reported in these studies as compared to our finding might be because of the countries commitment towards increasing household accessibility to adequately iodized salt.…”
Section: Discussionmentioning
confidence: 58%
“…However, this finding is lower than the findings from India 60.1% [23], Albania 60.41% [13], Ghana 75.6% [24], Kazakhstan 77.3% [25], and Nigeria 91% [26] of the households that were using adequately iodized salt. The explanation for the higher proportion of iodized salt consumption reported in these studies as compared to our finding might be because of the countries commitment towards increasing household accessibility to adequately iodized salt.…”
Section: Discussionmentioning
confidence: 58%
“…This finding showed poor knowledge in agreement with the study conducted by DeZoysa, et al which reported that 40% of respondent had poor knowledge on iodized salts and the importance of iodine in diet (DeZoysa et al, 2015). Buxton et al found that the knowledge of iodized salt was quite high, as 72% of the respondents knew that not every salt contains iodine (Buxton et al, 2012). The study conducted by Gerensea et al in Hawelti Kebelle shows that majority (94%) of the respondents have heard about iodized salt (Gerensea et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Data entry was made using Statistical Package for Social Scientists (SPSS) version 23.0 and descriptive statistic tests were done for the items which were summarized by frequencies and percentages (Buxton and Baguune, 2012).…”
Section: Discussionmentioning
confidence: 99%